APPLICATION SIMPLE ADDITIVE WEIGHTING (SAW) METHOD ON DESIGN OF DECISION SUPPORT SYSTEM FOR TEACHER PERFORMANCE ASSESSMENT - Munawaroh, Azizah; Sunardiyo, Said; Isdiyarto, Isdiyarto (Edu Komputika Journal, 2017)
Teacher’s Performance Assessment (PKG) is an ability assessment process of teachers to apply the competencies and skills include pedagogical, personality, social, and professional aspects. The results of the assessment then processed by PKG’s team to produce a final value which is useful in the process of career development, promotion and functional position. Therefore, systems are needed to process the results of PKG. Based on the situation, this research is intended to make decision support system of teacher’s performance assessment that can help the PKG team to manage PKG results and give priority to the selection of the best teachers based on their performance. This decision support system applying Simple Additive weighting (SAW) method to determine the priority of the best teachers. The concept of SAW method is to find a weighted sum of the performance rating for each alternative (teacher) on all attributes. The system is made using System Development Life Cycle (SDLC) development methods which consists of the analysis, design, code, test, and maintenance are implemented with the PHP and MySQL programming language. Tests performed on this system is blackbox testing and comparison.The results obtained from blackbox testing 100% valid, which means all of the functional system is running well. The results of comparative testing 100% valid because it has been adapted to the calculation based on PERMENEGPAN 16/2009.The system has been tested at the high school State an equals Wonosobo regency as end users, with an average yield of 87.69% of user response. Based on the research, the conclusion are taken that the decision support system with SAW method useful to help PKG team to cultivate the best prioritize of teacher assessment effectively and efficiently based on test results blackbox, comparison and analysis of the usefulness of the system user responses.